SELF-CONFIDENCE OF GRADE V ELEMENTARY SCHOOL STUDENTS IN LEARNING USING THE ROLE-PLAYING MODEL - Pratiwi Dwi Santi , Dina; Aenul Hayati, Auliya; Dyah Ayu Pitaloka, Indah; Rusma , Puputh (Cirebon International Conference on Education and Economics Proceeding, 2024)
Based on the results of observations of fifth grade students of SDN Bima Kota Cirebon, several problems were found such as most students were still shy when asked to come forward to the front of the class, lack of enthusiasm in the learning process, and not on time for submitting questions. In addition, students were nervous when performing in front of the class, students who did not ask questions after the teacher explained the subject matter, students who were silent when the teacher asked questions, students who were hesitant in expressing opinions in front of the class, students who looked anxious when the teacher gave quizzes/questions, and hesitated if the teacher referred students to come forward. Whereas a confident character will make individuals feel optimistic and able to make adjustments to their social environment. This study aims to determine how students' self-confidence in learning using the role-playing model. This research was conducted at SDN Bima Cirebon City with a total of 15 students per session. This research is descriptive qualitative research and the data collection technique used is a questionnaire about student self-confidence in thematic learning. The results showed that students showed their identity in the learning process and were able to understand the material presented by the teacher. In addition, learning with the role-playing model, students' confidence level will be better.